Modulation of Locomotor Activation by the Rostromedial Tegmental Nucleus - Lavezzi, Heather N (Neuropsychopharmacology, 2015)
The rostromedial tegmental nucleus (RMTg) is a strong inhibitor of dopamine neurons in the ventral tegmental area (VTA) reported to influence neurobiological and behavioral responses to reward omission, aversive and fear-eliciting stimuli, and certain drugs of abuse. Insofar as previous studies implicate ventral mesencephalic dopamine neurons as an essential component of locomotor activation, we hypothesized that the RMTg also should modulate locomotion activation. We observed that bilateral infusions into the RMTg of the gamma-aminobutyric acid A (GABA(A)) agonist, muscimol, indeed activate locomotion. Alternatively, bilateral RMTg infusions of the GABA(A) receptor antagonist, bicuculline, suppress robust activations of locomotion elicited in two distinct ways: (1) by disinhibitory stimulation of neurons in the lateral preoptic area and (2) by return of rats to an environment previously paired with amphetamine administration. The possibility that suppressive locomotor effects of RMTg bicuculline infusions were due to unintended spread of drug to the nearby VTA was falsified by a control experiment showing that bilateral infusions of bicuculline into the VTA produce activation rather than suppression of locomotion. These results objectively implicate the RMTg in the regulation of locomotor activation. The effect is important because much evidence reported in the literature suggests that locomotor activation can be an involuntary behavioral expression of expectation and/or want without which the willingness to execute adaptive behaviors is impaired.